Using plasmonically generated carriers as redox equivalents. (January 2020) - Yu, Sungju; Mohan, Varun; Jain, Prashant K.
Abstract: Abstract : Nanostructures of plasmonic metals naturally combine strong light–matter interactions with catalytic activity, enabling new opportunities for light harvesting, catalytic chemistry, and artificial photosynthesis. Numerous studies have demonstrated that the optical excitation of localized surface plasmons generates hot electrons that can activate adsorbates triggering or facilitating chemical reactions on the surface of the nanoparticle. Going beyond such hot-electron-activated chemistry, a body of studies has shown that electron and hole carriers can be harvested from a plasmonically excited nanoparticle and utilized as redox equivalents for driving chemical reactions involving charge transfer. This article reviews such photoredox chemistry driven by plasmonic excitation of metal nanoparticles. Under certain conditions, a plasmonically excited nanoparticle can catalyze multielectron, multiproton transformations such as the photosynthesis of CO2 to hydrocarbons. We describe how the free energy of plasmonically generated charge carriers can be harvested and utilized for thermodynamically uphill reactions involving the formation of energy-rich chemical bonds or the development of molecular complexity. We end with a discussion of future opportunities in plasmon-excitation-driven photoredox chemistry.